2005
DOI: 10.1111/j.1600-0668.2005.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of formaldehyde emission from building finishing materials at various temperatures in under heating system; ONDOL

Abstract: Koreans spend most of their time sitting on ONDOL (heated) floors, with their buttocks always in contact with the floor surface. The flooring materials are exposed to high temperatures (37-50 degrees C) why the effect of bake-out is rapid. The emission of formaldehyde from furniture materials are more important for the IAQ because usually MDF and particleboard of E2 grade are being used as furniture materials in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 14 publications
1
51
1
1
Order By: Relevance
“…Sin embargo, se identificó una mayor concentración de formaldehído en viviendas con muebles de madera maciza, aglomerada o contrachapada (plywood, término en inglés). Se espera que la emisión de formaldehído disminuya conforme pasa el tiempo (Kim y Kim 2005), sin embargo la madera es una de sus principales fuentes de emisión en interiores.…”
Section: Discussionunclassified
“…Sin embargo, se identificó una mayor concentración de formaldehído en viviendas con muebles de madera maciza, aglomerada o contrachapada (plywood, término en inglés). Se espera que la emisión de formaldehído disminuya conforme pasa el tiempo (Kim y Kim 2005), sin embargo la madera es una de sus principales fuentes de emisión en interiores.…”
Section: Discussionunclassified
“…The type of model was SEF, and the control model was DKC18. Figure 2 shows the testing environment, in the laboratory, as described by Kim and Kim (2005). In the lab, a copper pipe was installed with a narrow pitch in a cement mortar.…”
Section: Testing Environment and Equipmentmentioning
confidence: 99%
“…The heat for a radiant floor heating system is provided by hot water, which runs through an X-L pipe, an enclosed electric heating liquid pipe installed under cement mortar board (Kim and Kim 2005). The heating system controls consist of a central control and an indoor control (Olesen 2000).…”
Section: Introductionmentioning
confidence: 99%
“…After occupancy, the concentrations were higher in the winter than in the summer (Chun et al, 2005). Kim et al (2005) has investigated the effect of various temperatures on formaldehyde emission from flooring materials by the desiccator method, and also shown that flooring materials at high temperature had less formaldehyde emission rates than flooring materials at low temperature after four weeks. Zhang et al (2007) showed that temperature has significant effect on the VOC emission parameters of dry building materials by experimental and theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%